2023
DOI: 10.1371/journal.pgph.0001418
|View full text |Cite
|
Sign up to set email alerts
|

Striving towards true equity in global health: A checklist for bilateral research partnerships

Abstract: Interest in “global health” among schools of medicine, public health, and other health disciplines in high-income countries (HIC) continues to rise. Persistent power imbalances, racism, and maintenance of colonialism/neocolonialism plague global health efforts, including global health scholarship. Scholarly projects conducted in low- and middle-income countries (LMIC) by trainees at these schools in HIC often exacerbate these problems. Drawing on published literature and shared experiences, we review key inequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 71 publications
(118 reference statements)
0
17
0
Order By: Relevance
“…That decision to change the research approach and design emerged in a 2‐day meeting held in Boston, USA, where investigators from all partners/institutions attended and presented their opinions. Those collaborative meetings for study design and development were only achieved through mutual respect, trust, partnership and transparency, aligned with the four principles recently highlighted by Hodson and colleagues on equitable partnerships 20 …”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…That decision to change the research approach and design emerged in a 2‐day meeting held in Boston, USA, where investigators from all partners/institutions attended and presented their opinions. Those collaborative meetings for study design and development were only achieved through mutual respect, trust, partnership and transparency, aligned with the four principles recently highlighted by Hodson and colleagues on equitable partnerships 20 …”
Section: Discussionmentioning
confidence: 83%
“…Those collaborative meetings for study design and development were only achieved through mutual respect, trust, partnership and transparency, aligned with the four principles recently highlighted by Hodson and colleagues on equitable partnerships. 20 Secondly, through protocol development and training curricula, we were able to ensure that consistent approaches were being used across the study. In July 2019, we conducted standardised training across all partners focused on ethics and data collection with didactic sessions including role play.…”
Section: Lesson #3: a Mixed Methods Approach Adds Value To The Study ...mentioning
confidence: 99%
“…However, as Gloyd argued, major aspects of colonialism are still evident, and global health can sometimes be just a new label for old practices [ 11 ]. The persistent power imbalances, socio-economic inequities, racism, and new colonialism contribute to global health inequities [ 12 ]. HICs in the North are often viewed as centers for top-quality global health education, training, and research.…”
Section: Decolonizing Global Health: Addressing Power Imbalances and ...mentioning
confidence: 99%
“…Kumar et al emphasized the need for increased transparency in funding for global health research and for researchers in recipient countries to take a leadership role in controlling funds and resources [ 16 ]. Hodson et al suggested prioritizing direct funding for researchers in LMICs and establishing mechanisms for LMIC institutions and researchers to lead direct funding [ 12 ]. These recommendations not only support Gloyd’s observations but also offer practical guidance for future Chinese endeavors.…”
Section: Implications Of Decolonization For Chinese Academic Global H...mentioning
confidence: 99%
See 1 more Smart Citation